Implementasi Pasal 4 Angka 1 Undang-Undang Nomor 8 Tahun 1999 terhadap Kenyamanan dan Keamanan dalam Penertiban Parkir di Jalan Panjaitan Kota Gorontalo - Aditya Sharul Ramadhan; Nirwan Junus; Sri Nanang Meiske Kamba (Lembaga Yasin AlSys, 2026)
This study examines the implementation of Article 4(1) of Law Number 8 of 1999 on Consumer Protection in the regulation and control of parking as an effort to fulfill consumer rights, particularly the right to safety and comfort in using parking infrastructure. Problems arise when breaches of obligation by parking attendants occur and they refuse to assume responsibility for their negligence, raising questions about the form of dispute resolution when no accountability is taken by the attendant. This study employed a socio-legal approach with an empirical legal research design to analyze the implementation of Article 4(1) of Law Number 8 of 1999 on Consumer Protection in parking regulation and to investigate monitoring and law enforcement activities related to on-street parking on Panjaitan Street in Gorontalo City. Field data and relevant regulations were analyzed to describe patterns in the fulfillment of legal obligations by parking attendants and the realization of consumer rights. The findings show that parking activities have been routinely monitored by the Transportation Agency; however, implementation remains constrained by limited monitoring facilities and the absence of a clear mechanism for allocating responsibility for damage to or loss of consumers’ vehicles. In conclusion, the implementation of consumer protection provisions in parking practices on Panjaitan Street has not yet fully ensured legal certainty of protection for consumers, thereby necessitating stronger monitoring mechanisms and more explicit formulations of parking attendants’ liability within the framework of consumer protection law enforcement.